Histologically proven epithelial ingrowth in failed Descemet stripping automated endothelial keratoplasty (DSAEK) managed by repeat DSAEK - Ghosh, Saurabh (Dove Medical Press, 2013)
PURPOSE: To report a case of corneal graft failure due to epithelial ingrowth after an uneventful combined Descemet stripping automated endothelial keratoplasty (DSAEK) and phacoemulsification cataract surgery with intraocular lens implant treated successfully with a repeat DSAEK. METHODS: A 77-year-old male patient underwent combined DSAEK and phacoemulsification with intraocular lens implant implantation for Fuchs’ endothelial dystrophy plus cataract in the right eye. The donor cornea was cut on the Moria ALTK system and introduced using a suture pull-through technique. After an episode of endothelial rejection, the graft failed, with signs suggesting epithelial ingrowth. It was stripped from the host cornea using a Descemet’s membrane stripper, and a Simcoe irrigation-aspiration cannula was used to remove all traces of interface material. The excised lenticule was examined histologically using a hematoxylin and eosin stain. RESULT: The patient regained and maintained excellent visual acuity with no sign of recurrence of epithelial ingrowth. Histopathological evaluation of the donor tissue of the first graft showed epithelial ingrowth on the stromal surface of the graft and very few endothelial cells, in keeping with the diagnosis of graft failure. CONCLUSION: Epithelial ingrowth is a possible cause of endothelial graft failure, but histologically proven cases are rare. Surgical intervention can achieve successful clearance, with the potential for cure and an excellent outcome.